In search of the original text in Mark 9:38 - W. M. A. Hendriks (Acta Theologica)
The text-critical situation of Mark 9:38 is very complicated. This complex situation already becomes evident in the different readings of the critical editions. While there is almost no variation in the first part of the verse, the critical editions offer four different readings in the last part of it. So there is until now no consensus at all. The question remains which text appears to be the more original one. Several scholars – such as Vaganay, Duplacy, Amphoux, and others – in search of the original text of Mark – opt for a so called Western text, the main stream still prefers the Neutral text of Westcott and Hort. A text-critical analysis of Mark 9:38 may provide an answer to this question.